Uji Aktivitas Antioksidan Ekstrak Etanol Biji Kakao (Theobroma cacao L.) Dengan Menggunakan Metode DPPH - Sy. Tasanif, Siti Rachmawati (Makassar Natural Product Journal (MNPJ), 2024)
Cocoa bean is a plant that contains phenolic and flavonoid chemical compounds which can act as natural antioxidants. In addition, cocoa beans can also be used as anti-inflammatory drugs, obesity, diabetes and colitis. The purpose of this study was to determine the antioxidant activity of the ethanol extract of cocoa beans (Theobroma cacao L.). This research is a laboratory-scale experimental study by testing the antioxidant activity using the DPPH method and measured by spectrophotometry. The stages in this study were sample preparation, phytochemical screening, qualitative test and quantitative test of antioxidant activity using DPPH. The results obtained from this study were positive cocoa beans containing phenols and flavonoids. The DPPH qualitative test results were marked by a change in color with a purple background and the sample was yellow with an Rf value of 0.36 and the quantitative test results for antioxidant activity obtained were the ethanol extract of cocoa beans which had an IC50 value of 159.118 µg/ml indicating that this sample had activity weak antioxidants.